2003
DOI: 10.1515/cclm.2003.049
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenin and Gestational Trophoblastic Tumors, a Promising Prognostic Marker

Abstract: The aim of this study was to evaluate the diagnostic and prognostic values of serum angiogenin concentration in cases with gestational trophoblastic diseases (GTDs). Seventy-two patients with GTDs and 20 first trimester healthy pregnant women (controls) participated in this study. According to the WHO scoring system, GTDs were subgrouped into 24 hydatiform mole spontaneous regression (HMSR), 18 postmolar gestational trophoblastic tumors of high risk (PMHR), 16 low-risk choriocarcinoma, and 14 high-risk chorioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
(15 reference statements)
1
4
0
Order By: Relevance
“…Moreover, we demonstrated that ANG localized to the villous syncytiotrophoblast cells in GTD placenta tissues and maternal serum similar to that in normal patients by using IHC. Shaarawy et al found that the serum ANG concentration showed diagnostic and prognostic values for the differential diagnosis of GTD, [18] which was consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Moreover, we demonstrated that ANG localized to the villous syncytiotrophoblast cells in GTD placenta tissues and maternal serum similar to that in normal patients by using IHC. Shaarawy et al found that the serum ANG concentration showed diagnostic and prognostic values for the differential diagnosis of GTD, [18] which was consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
“…[15][16][17] Serum ANG levels in choriocarcinoma cases were significantly higher than in healthy pregnant women. [18] However, its expression in GTN tissues and mechanism remain unknown, as cases are rare. [19] Human placentation processes require a balance between the degradation of the maternal decidual vasculature and the concurrent angiogenesis directed by the developing embryo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum angiogenin level in low‐ and high‐risk patients with choriocarcinoma is significantly higher and correlates with disease progression (79) . Moles and choriocarcinoma show marked elevations of serum IL‐1β, IL‐6, and TNF‐α with disease progression (80) .…”
Section: Biologic Significancementioning
confidence: 99%
“…Angiogenin (ANG) has been extensively reported across a variety of malignant diseases, including gestational trophoblast neoplasia ( 5 , 6 ), prostate cancer ( 7 , 8 ), bladder cancer ( 9–13 ), nasopharyngeal carcinoma ( 14 , 15 ), colorectal cancer ( 16 , 17 ), hepatocellular carcinoma ( 18 ), pancreatic cancer ( 19 ), renal cell carcinoma ( 20 ), gastric and colon cancer ( 21 ), lung cancer ( 22 , 23 ), breast cancer ( 24 , 25 ), multiple myeloma ( 26 ), lymphoma ( 27 , 28 ), oral cancer ( 29 ), neuroblastoma ( 30 ), melanoma ( 31 ), cervical cancer ( 32 ), and laryngeal carcinoma ( 33 ). ANG, also termed RNase5, belongs to the RNase A superfamily, whose family members primarily play roles in ribonucleolytic activity.…”
Section: Introductionmentioning
confidence: 99%